Pengembangan Media Pembelajaran Interaktif Berbasis Emaze Menggunakan Pendekatan Kontekstual pada Materi Bilangan Bulat Kelas VII SMP Negeri 4 Kubung - Hayati, Sismi; Pratiwi, Reno Warni; Oktavinora, Rita (Indo-MathEdu Intellectuals Journal, 2025)
This research is motivated by the lack of understanding of the material by students, student boredom in learning, limited learning resources and the use of technology in learning that has not been maximized. The purpose of this study is to produce interactive learning media based on emaze using a contextual approach to integer material for class VII of SMP Negeri 4 Kubung. This type of research is research and development, using PLOOMP development consisting of three stages (Preliminary Research Phase, Design & Develop Prototype, Evaluation). The instruments used are teacher and student interview questionnaires, validation questionnaires consisting of language experts, media experts and material experts. The development of interactive learning media based on emaze goes through three stages. The first stage is preliminary analysis, namely: needs analysis, curriculum analysis, concept analysis, and analysis of student characteristics. The second stage: Creation and development, namely self-evaluation and expert validation. The third stage of evaluation is an assessment of whether interactive learning media based on emaze is valid for use. Based on the results of the validation of the material expert questionnaire 96.67%, media experts 83.88%, and language experts 88.00%, so that the average of the four validators is 89.51%. The results of this validation indicate that the developed emaze-Based Interactive Learning Media has been tested for quality and declared valid for use in the learning process.